Advances in TAVR: A Review of Current Evidence and Clinical Implications - Atiq Ur Rehman,; Faiz Ullah,; Khan, Rahim Dil; Khan, Muhammad Idrees; Khan, Ajmal (Indus Journal of Bioscience Research, 2025)
Introduction: Transcatheter aortic valve replacement (TAVR) has taken place alongside surgical aortic valve replacement (SAVR) as an effective therapy for aortic stenosis – especially for patients with high and intermediate surgical risk. Subsequent developments have expanded these indications to include low-risk and other technically challenging subgroups. Objective: To evaluate the clinical outcomes and procedural success of TAVR in a tertiary care hospital in Pakistan. Materials and Method: This prospective observational study was conducted at Hayatabad Medical Complex Peshawar, Pakistan from January, 2024 to June, 2024. The inclusion criteria were symptomatic severe aortic stenosis patients, and they underwent TAVR with either balloon-expandable or self-expanding valves. Results: In 108 patients, the procedural success rate was 97.2%. Mean aortic valve area increased post-procedure, and there were low short-term adverse events mortality 1.9%, stroke 2.8%, and pacemaker implantation 10.2%. Conclusion: Real-world studies have shown that TAVR is a safe and effective approach for aortic stenosis in patients and supports procedural and clinical success.